2007
DOI: 10.1158/1078-0432.ccr-06-0659
|View full text |Cite
|
Sign up to set email alerts
|

Clonal and Parallel Evolution of Primary Lung Cancers and Their Metastases Revealed by Molecular Dissection of Cancer Cells

Abstract: Purpose: Several models of cancer progression, including clonal evolution, parallel evolution, and same-gene models, have been proposed to date. The purpose of this study is to investigate the authenticity of these models by comparison of accumulated genetic alterations between primary and corresponding metastatic lung cancers. Experimental Design: A whole-genome allelic imbalance scanning using a high-resolution single nucleotide polymorphism array and mutational analysis of the p53, EGFR, and KRAS genes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
38
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 39 publications
4
38
0
Order By: Relevance
“…Within individual patients, most mutations in primary tumors and metastases are identical, but some are unique to each; increasing degree of tumor cell chromosomal aberration correlates with more malignant properties; and recurrences contain the mutations seen before in primary tumors along with additional ones. 53,[59][60] Studies of pre-malignant lesions such as colorectal adenomas have similarly found that more mutations tend to occur in more advanced neoplasms, 61 indicating that clonal evolution likely occurs during tumorigenesis and may therefore continue during tumor progression.…”
Section: The Cancer Stem Cell Hypothesismentioning
confidence: 99%
“…Within individual patients, most mutations in primary tumors and metastases are identical, but some are unique to each; increasing degree of tumor cell chromosomal aberration correlates with more malignant properties; and recurrences contain the mutations seen before in primary tumors along with additional ones. 53,[59][60] Studies of pre-malignant lesions such as colorectal adenomas have similarly found that more mutations tend to occur in more advanced neoplasms, 61 indicating that clonal evolution likely occurs during tumorigenesis and may therefore continue during tumor progression.…”
Section: The Cancer Stem Cell Hypothesismentioning
confidence: 99%
“…5,6 Despite the widely accepted paradigm that tumor progression to metastasis occurs through linear clonal evolution, other mechanisms for this process have also been proposed. The parallel evolution model suggests that cells with metastatic potential separate from the primary tumor at an early stage in development and evolve independently from the primary tumor.7 Evidence supporting this has come from genomic analysis of breast and renal cell metastases, in which genetic profiles were found to be dissimilar to those of the primary tumors from the same patient.7-9 The parallel evolution model has also been used to explain the pattern of metastases in several other epithelial tumors, 3 although not ovarian cancer. However, in vivo studies argue against the viability of disseminated tumor cells; in a murine model, cells shed from tumors have reduced clonegenicity, resistance to apoptosis and to the formation of tumors.…”
mentioning
confidence: 99%
“…7-9 The parallel evolution model has also been used to explain the pattern of metastases in several other epithelial tumors, 3 although not ovarian cancer. However, in vivo studies argue against the viability of disseminated tumor cells; in a murine model, cells shed from tumors have reduced clonegenicity, resistance to apoptosis and to the formation of tumors.…”
mentioning
confidence: 99%
See 2 more Smart Citations